2
$\begingroup$

I have given following recurrence relation:

$$a_{n+1} = (n+1)a_n + n!$$ where $a_0 = 0$

I had invoked given relation with exponential generating function, such as:

$$g(x) = \sum_{n=0}^\infty a_n {x^n\over n!} \\= \sum_{n=1}^\infty a_n {x^n\over n!} + a_0 \\= \sum_{n=0}^\infty a_{n+1} {x^{n+1}\over (n+1)!}\\=x\sum_{n=0}^\infty a_n {x^n\over n!}+\sum_{n=0}^\infty{1\over n+1}x^{n+1}$$ thus, $$g(x) = xg(x) + x+\frac{x^2}{2} + \frac{x^3}{3} +\cdots$$ therefore, $$g(x) = {1\over 1-x}(x+\frac{x^2}{2}+\frac{x^3}{3} + \cdots) \tag{1}$$

Now from this $g(x)$ I want to draw out explicit formula of $a_n$ but I can't image the way how I can change RHS of $(1)$ into form of $a_nx^n/n!$

Where should I start from?

$\endgroup$
  • $\begingroup$ You get that $g(x) = \sum H_n x^n$ is the ordinary generating function of the harmonic numbers $H_n = \sum_{k=1}^n \frac{1}{k}$, so $a_n = n! H_n$. I don't think you can say much more than that. $\endgroup$ – Qiaochu Yuan Nov 27 '17 at 0:02
1
$\begingroup$

If we divide by $(n+1)!$, we get $$ \frac{a_{n+1}}{(n+1)!}=\frac{a_n}{n!}+\frac1{n+1} $$ Thus, $$ \frac{a_n}{n!}=C+H_n $$ The condition $a_0=0$ implies that $C=0$. Therefore, $$ a_n=n!\,H_n $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.